Quantitative assessment of the effect of uracil-DNA glycosylase on amplicon DNA degradation and RNA amplification in reverse transcription-PCR - Kleiboeker, Steven B (BioMed Central, 2005)
Although PCR and RT-PCR provided a valuable approach for detection of pathogens, the high level of sensitivity of these assays also makes them prone to false positive results. In addition to cross-contamination with true positive samples, false positive results are also possible due to "carry-over" contamination of samples with amplicon DNA generated by previous reactions. To reduce this source of false positives, amplicon generated by reactions in which dUTP was substituted for dTTP can be degraded by uracil DNA glycosylase (UNG). UNG does not degrade RNA but will cleave contaminating uracil-containing DNA while leaving thymine-containing DNA intact. The availability of heat-labile UNG makes use of this approach feasible for RT-PCR. In this study, real-time RT-PCR was used to quantify UNG degradation of amplicon DNA and the effect of UNG on RNA detection. Using the manufacturers' recommended conditions, complete degradation of DNA was not observed for samples containing 250 copies of amplicon DNA. Doubling the UNG concentration resulted in degradation of the two lowest concentrations of DNA tested, but also resulted in an increase of 1.94 cycles in the C(T )for RNA detection. To improve DNA degradation while minimizing the effect on RNA detection, a series of time, temperature and enzyme concentrations were evaluated. Optimal conditions were found to be 0.25 U UNG per 25 μl reaction with a 20 min, 30°C incubation prior to RT-PCR. Under these conditions, high concentrations of amplicon DNA could be degraded while the C(T )for RNA detection was increased by 1.2 cycles.